Masi's Law - Hazak, Aaro; Møller, Adam Jacobi (South Africa, 2012)
Masiphumelele, or Masi, is a township near Cape Town, South Africa. High crime rates and limited access to the law enforcement and police officers have necessitated community-based security measures. The volunteer group Bambanani and Street Committee volunteer movements help to fight against the crime in the Masi community.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films